Nutritional quality of diet and academic performance in Chilean students - Correa-Burrows, Paulina (Bull World Health Organ, 2016)
OBJECTIVE: To explore associations between the nutritional quality of diet at age 16 years and academic performance in students from Santiago, Chile. METHODS: We assessed the nutritional quality of diet, using a validated food frequency questionnaire, in 395 students aged 16.8 ± 0.5 years. Depending on the amount of saturated fat, fibre, sugar and salt in the foods, diet was categorized as unhealthy, fair or healthy. Academic performance was assessed using high school grade-point average (GPA) and tests for college admission in language and mathematics. Academic results on or above the 75th percentile in our sample were considered good academic performance. We tested associations between nutritional quality of diet and good academic performance using logistic regression models. We considered sociodemographic, educational and body-mass index (BMI) factors as potential confounders. FINDINGS: After controlling for potential confounding factors, an unhealthy diet at age 16 years was associated with reduced academic performance. Compared to participants with healthy diets, those with unhealthy diets were significantly less likely to perform well based on language tests (odds ratio, OR: 0.42; 95% confidence interval, CI: 0.18–0.98) mathematics tests (OR: 0.35; 95% CI: 0.15–0.82) or GPA (OR: 0.22; 95% CI: 0.09–0.56). CONCLUSION: In our sample, excessive consumption of energy-dense, low-fibre, high-fat foods at age 16 years was associated with reduced academic performance.